Patient hand hygiene experiences in a primary care centre in Ireland during COVID-19 - Kinsella, Anne-Marie; O'Reilly, Pauline (International Journal of Infection Control, 2024)
The implementation of proper hand hygiene (HH) has been shown to reduce the risk of developing healthcare-associated infections. There is an increased awareness of the importance of HH since the onset of COVID-19. This study used an interpretive descriptive qualitative design to explore patients’ experiences of healthc workers’ (HCWs’) HH practices in a primary care centre in Ireland during COVID-19. The data were collected from 12 participants using in-depth, semi-structured interviews and analysed using reflexive thematic analysis. Two themes were constructed, each with two subthemes. Theme 1, ‘Focus and Awareness’, had the subthemes ‘Hand Hygiene and Patient’s Awareness’ and ‘Positive Effects of COVID-19’. Theme 2, ‘Breaking Barriers’, had the subthemes ‘Fear of Repercussions’ and ‘Responsibility and Empowerment’. Patients believed they should have a role when it comes to ensuring correct HH is performed during their episode of care. Barriers to this included the perceived reaction of HCWs to the feedback and a lack of knowledge of the five moments of hand hygiene.